PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA LPK MONARCH DALUNG-BALI - I Ketut Sudama; Ida Ketut Kusumawijaya (Journal Research of Management, 2020)
This study aims to investigate the influence of motivation, labor discipline, and work environment toward employee performance at LPK Monarch Dalung-Bali. The sampling technique used in this study is census technique taken from all employees at LPK Monarch Dalung-Bali as many as 38 people. The analysis technique used in this study is Multiple Linear Regression with Statistical Package for the Social Sciences (SPSS) versi 15.0 for windows. The results showed that 1) motivation has a positive and significant effect on employee performance at LPK Monarch Dalung-Bali. 2) Labor discipline has a positive and significant effect on employee performance at LPK Monarch Dalung-Bali. 3) Work environment has a positive and significant effect on employee performance at LPK Monarch DalungBali. The advices in this study indicate that the company could be defended and improved the motivation, labor discipline, and work environment in increasing employee performance. The improvement of employee motivation had better do by giving the salary based on the competence, workload, and achievement. The improvement of labor discipline should be done by increasing the understanding of employee on the regulation in company. Furthermore, the improvement of work environment could be done by adding ventilations and plants around the room to get a fluent air circulation and make the employee more comfortable to work.